Implementasi Aparat Pengawas Intern Pemerintah Dalam Meningkatkan Akuntabilitas Dan Transparansi Penyelenggaraan Pemerintah Daerah (Studi Di Inspektorat Daerah Kabupaten Asahan) - Lubis, Sofyan Soury; Bahmid, Bahmid (Universitas Batanghari Jambi, 2024)
The Government Internal Supervisory Apparatus (APIP) in increasing accountability and transparency of regional finances, especially those carried out at the Regional Inspectorate of Asahan Regency, has an important urgency in financial accountability, because the Regional Inspectorate is responsible for ensuring that all regional government finances are carried out transparently and in accordance with applicable regulation. This research aims to identify the extent to which internal supervisory officials are successful in ensuring financial accountability in Asahan Regency. This research can also make a significant contribution to efforts to improve regional financial governance as a whole. The method used is empirical supported by interviews and data collection by means of documentation studies, literature studies and interviews. The authority of the Government Internal Apparatus (APIP) to increase accountability and transparency in Asahan Regency, by providing quality assurance consisting of audits, monitoring, evaluation, monitoring, reviews, implementation of the Whistle Blowing System and Consulting Partners which consists of assistance and mentoring as well as consultations.